2021
DOI: 10.5114/aoms/132950
|View full text |Cite
|
Sign up to set email alerts
|

Improved COVID-19 ICU admission and mortality outcomes following treatment with statins: a systematic review and meta-analysis

Abstract: IntroductionApproximately 1% of the world population has now been infected by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19). With cases still rising and vaccines just beginning to rollout, we are still several months away from seeing reductions in daily case numbers, hospitalisations, and mortality. Therefore, there is a still an urgent need to control the disease spread by repurposing existing therapeutics. Owing to antiviral, anti-inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 96 publications
3
44
0
Order By: Relevance
“…This study could also open the discussion about possible treatments of this dysfunction: it is known that physical exercise can improve endothelial function [30,31], and rehabilitation attempts could lead to a beneficial improvement as well. Other treatments that could produce improvement are specific classes of dietary supplements [32] or drugs [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…This study could also open the discussion about possible treatments of this dysfunction: it is known that physical exercise can improve endothelial function [30,31], and rehabilitation attempts could lead to a beneficial improvement as well. Other treatments that could produce improvement are specific classes of dietary supplements [32] or drugs [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…While hyperlipidemia and obesity are common co-morbidities with negative impacts on most associated pathologies [14], in the present study patients with hyperlipidemia were clearly protected from mortality due to COVID-19, with a 60% lesser probability of death compared to other patients (OR = 0.38). Known to reduce COVID-19 mortality [15][16][17], statins that were prescribed to hyperlipidemic patients may account for patients' protection against COVID-19 associated death. In addition to their primary lipid-lowering effect, statins appear to regulate vasodilation via a receptor of the novel coronavirus, angiotensin-converting enzyme 2 (ACE2) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in our study, none of the affected FH subjects required hospitalization; future studies in larger cohorts of FH subjects are needed to confirm and explain this preliminary finding. However, previous findings showed that among subjects with SARS-CoV-2 infection requiring hospitalization, statin users were associated with lower mortality than non-statin users [ 18 , 19 , 20 ]. Taking these findings into consideration, a possible hypothesis could be that subjects with a long duration of statin therapy, such as FH subjects, could be characterized by a reduced need for hospitalization [ 21 ].…”
Section: Discussionmentioning
confidence: 99%